Competency as A Basis for Human Resource Planning and Performance Optimization in Bumdes Cikalong - Dewi Kania; Zulganef; Suadhe Rahmat Siregar (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
The gap between ideal and actual employee competencies remains a barrier for BUMDes (Village-Owned Enterprises) in strengthening the governance and performance of village economic services. This study stems from the urgency of addressing the competency mismatch in Cikalong BUMDes to make the organization more adaptive, accountable, and innovative. The research aims to analyze the implementation of competency-based HR planning and its supporting and inhibiting factors in optimizing performance. The theoretical study combines Competency Theory (Spencer & Spencer), Strategic Human Resource Management (Wright & McMahan), and performance theory (Campbell). The method used is a qualitative case study with data collection through in-depth interviews, participant observation, and documentation. Informants were selected purposively; analysis follows the interactive model of Miles and Huberman and triangulation. The findings indicate that competency mapping and appropriate role placement increase motivation, loyalty, and productivity, but are hampered by unclear competency standards, work culture resistance, and weak HR information systems. Consequently, competency-based planning needs to be positioned as a transformational, rather than administrative, strategy, consistently and sustainably.